Thinking way and method of diagnosis and treatment in Traditional Chinese Medicine and its implications for narrative nursing (中医诊疗思维对叙事护理的启示) - WANG Zixu (王子旭) (中西医结合护理)
This article discussed the thinking way and method of diagnosis and treatment in Traditional Chinese Medicine and its implications for narrative nursing, so as to provide practical methods with Traditional Chinese Medicine characteristics for narrative nursing practice. (本文就中医诊疗思维, 如司外揣内、见微知著、知常达变等, 对临床中的叙事护理实践的促进作用及启示作以阐述, 以期为叙事护理实践提供具有中医特色的实践方法。)